PEMBANGUNAN EKONOMI WILAYAH DI KOTA MAKASSAR (STUDI KASUS DI KECAMATAN UJUNG PANDANG) - Ridwan Ridwan; Yosar Kardiat (Jurnal Pallangga Praja (JPP), 2020)
Regional economic development is absolutely necessary to accelerate economic growth in order tocatch up with the economic growth of the Maakassar City Region. Thus, it is expected that there will benew job opportunities and reduce unemployment. . Makassar City is the capital city of South SulawesiProvince. There are very big opportunities in order to take advantage of existing opportunitiescompared to other districts in South Sulawesi Province. This research is entitled “Regional EconomicDevelopment in Makassar City (Case Study in Ujung Pandang District)”. Where is the formulationof the problem. How does the planning apparatus design development in Makassar City? How is theimpact of development results in Makassar City so that it can be enjoyed by the people of MakassarCity? How does the Mayor of Makassar make a harmonious integration between the interests of theGovernment and the community? The research method used is a qualitative method?